MEMBANGUN APLIKASI CATATAN PERJALANAN SEDERHANA MENGGUNAKAN ANDROID STUDIO - Alifur Rahman; Efmi Maiyana (Journal of Innovation And Future Technology, 2025)
Traveling often creates valuable moments worth documenting, yet not everyone has an efficient way to record their experiences. This study aims to design and develop a simple travel journaling application called "My Journey" using Android Studio. The application is intended to provide a solution for users seeking an easy and organized way to document their travel experiences. The problem addressed is the lack of simple applications that offer intuitive features for personal travel journaling while prioritizing user convenience. To address this issue, the study employs the waterfall software development model, which includes phases of analysis, design, implementation, testing, and maintenance. "My Journey" is developed using Java for core functionality, XML for interface design, and JSON as the database for storing user data. The application's main features include the ability to add, view, edit, and delete travel notes. The development process emphasizes creating a user-friendly and straightforward interface. Testing results show that the application performs well on Android devices and meets user needs for documenting travel experiences. From a user perspective, the application provides an intuitive, efficient, and reliable experience. The study also identifies potential enhancements, such as integrating digital maps, cloud-based storage, and social sharing features to expand the application's functionality. With the outcomes achieved, "My Journey" demonstrates significant potential as an innovative solution in travel-based applications, particularly for users seeking a simple yet functional tool to record their travel moments.